Computer vision, imaging and computer graphics : theory and applications International Joint Conference, VISIGRAPP 2010, Angers, France, May 17-21, 2010. Revised Selected Papers - Richard, Paul; Braz, José (Communications in computer and information science, 2011)
This book constitutes the refereed proceedings of the International Conference, VISIGRAPP 2010, the Joint Conference on Computer Vision Theory and Applications (VISAPP), on Imaging Theory and Applications (IMAGAPP), and on Computer Graphics Theory and Applications (GRAPP), held in Angers, France, in May 2010. The 19 revised full papers presented together with two invited papers were carefully reviewed and selected. The papers are organized in topical sections on computer vision theory and applications; imaging theory and applications; computer graphics theory and applications; and information visualization theory and applications.